2018
DOI: 10.1186/s13104-018-3844-1
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence, antimicrobial susceptibility profile and predictors of asymptomatic bacteriuria among pregnant women in Adigrat General Hospital, Northern Ethiopia

Abstract: ObjectiveApproach to asymptomatic bacteriuria among pregnant women in Ethiopia is mainly based on clinical grounds and urine strip and microscopy tests. On top of this, the treatment is also on an empirical basis which may leads to an increased antimicrobial resistance. The aim of this study was to assess the prevalence, antimicrobial susceptibility profile and associated factors of asymptomatic bacteriuria among pregnant women attending antenatal clinic in Adigrat Hospital, Northern Ethiopia.ResultsOut of 259… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
44
7
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(76 citation statements)
references
References 30 publications
23
44
7
2
Order By: Relevance
“…Which show that most of the Gram-negative isolates were sensitive to ceftazidm, ceftriaxone, cefotaxime, amikacin, tobramycin and cipro oxacin and resistant to tetracycline and amoxicillin. However, our nding is in contrary to studies done in Kashmir [27], and Adigrat Northern Ethiopia [28]. Which show that most of the Gram-negative isolates were sensitive trimethoprim-sulfamethoxazole augmentin, nalidixic acid and gentamycin.…”
Section: Resultscontrasting
confidence: 99%
“…Which show that most of the Gram-negative isolates were sensitive to ceftazidm, ceftriaxone, cefotaxime, amikacin, tobramycin and cipro oxacin and resistant to tetracycline and amoxicillin. However, our nding is in contrary to studies done in Kashmir [27], and Adigrat Northern Ethiopia [28]. Which show that most of the Gram-negative isolates were sensitive trimethoprim-sulfamethoxazole augmentin, nalidixic acid and gentamycin.…”
Section: Resultscontrasting
confidence: 99%
“…Direction of wiping after genital wash, catheterization, and postcoital urination increase the odds of asymptomatic bacteriuria. is finding was consistent with previous studies from Adigrat, Ethiopia (21.2%) [5], and Ghana (17.5%) [14]. But it was relatively higher in other studies reported from Bahir Dar, Ethiopia (11.5%) [9], and countries such as India (13.2%) [15] and Nigeria (10.6%) [16].…”
Section: Discussionsupporting
confidence: 91%
“…Asymptomatic bacteriuria is one of the major risk factors for the development of UTIs during pregnancy which accounts for about 70% of the cases [5]. Globally, asymptomatic bacteriuria affects 2-10% of all pregnant women [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following publication of the original article [ 1 ], the authors reported that one of the authors’ names was spelled incorrectly. In this Correction the incorrect and correct author name are shown.…”
Section: Correction To: Bmc Res Notes (2018) 11:740 101186/s13104-01mentioning
confidence: 99%